Living Sufism of Sheikh Ahmad Mutamakkin in Tradition and Culture of Kajen Muslim Community - Alnashr, M Sofyan; Nisfa, Nia Lailin; Linnas, Mohammad Ghoffarul (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2025)
Sheikh Ahmad Mutamakkin was a prominent Islamic scholar who played a significant role in spreading Sufism in the northern coastal region of Central Java, particularly in Pati. This study aims to explore how the concept of "Living Sufism" is manifested through the integration of Sufi teachings into the traditions and culture of the Kajen Muslim community. Using a qualitative approach, data were collected through documentation, in-depth interviews, and direct observation. The findings reveal that Sheikh Mutamakkin's Sufism is deeply rooted in sharia, particularly in the context of fiqh, as evidenced by his work Arsy Muwahhidun. His teachings have been integrated into local traditions, pesantren education, and the architectural symbolism of the Jami' Kajen Mosque. In the modern era, Sheikh Mutamakkin's Sufism remains relevant as it offers a spiritual solution to the crisis of materialism and secularism. This study contributes to the understanding of how Sufism can be contextualized within local culture while maintaining its Islamic essence.